Pengembangan Media Diorama Berbasis Augmented Reality Untuk Meningkatkan Berpikir Reflektif Dan Self Regulation Pada Mapel IPAS SD - Inayatul Adhimah; Rarasaning Setianingsih; Rosmiati (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop and evaluate an Augmented Reality (AR)-based diorama learning media to enhance elementary students’ reflective thinking and self-regulation in IPAS learning. This study employed a Research and Development (R&D) approach adapted from Borg and Gall, followed by a one-group pretest-posttest design to examine effectiveness. The participants were third-grade elementary students. Data were collected through expert validation sheets, practicality questionnaires, and reflective thinking and self-regulation test. Data analysis was conducted using descriptive statistics and normalized gain (N-gain). The results indicate that the developed media achieved very high validity (M = 3.76) and practicality (M = 3.81). The effectiveness test shows significant improvement in reflective thinking (N-gain = 0.68) and self-regulation (N-gain = 0.71), both in ranged from moderate to high categories. These study contributes by positioning that the integration of concrete diorama media with AR technology effectively promotes interactive, students-centered learning and supports the development of higher-order thinking skill and learner autonomy. This research contributes an empirically validated instructional media model elementary IPAS context that integrates physical and digital learning environments to enhance both cognitive and self-regulated learning outcomes in elementary IPAS